Characterization of Beauty Salon Wastewater from Kwame Nkrumah University of Science and Technology, Kumasi, Ghana, and Its Surrounding Communities - Marian A. Nkansah; Francis Opoku; James H. Ephraim; David D. Wemegah; Luke P.M. Tetteh (SAGE Publishing, 2016)
Due to the increase in students' population over the years, the Kwame Nkrumah University of Science and Technology (KNUST), Kumasi, Ghana, and its surrounding communities have seen an increase in the number of beauty salons. The assessment of the quality of salon wastewater has received little attention, as a potential source of environmental and public health hazard, due to the lack of literature on this issue. The main aim of this study is to assess wastewater effluent characteristics in KNUST and its surrounding areas, in relation to its physicochemical and microbial parameters. A total of 48 wastewater samples were collected monthly in 250 L polystyrene bottles, over a two-month period from the KNUST and Ayigya, Ayeduase, and Bomso communities. Standard methods of American Public Health Association (APHA, 19th edition) were employed in the determination of the physicochemical parameters and microbial content of the wastewater samples. The results showed that all the sampling towns had mean chemical oxygen demand (COD; 60.04 ± 1.82 mg/L), biological oxygen demand (BOD; 30.03 ± 9.11 mg/L), dissolved oxygen (DO; 3.00 ± 0.53 mg/L), pH (9.55 ± 0.42), nitrate (5.42 ± 0.36 mg/L), phosphate (23.61 ± 0.16 mg/L), acidity (1.70 ± 0.01 mg/L), alkalinity (70.88 ± 2.59 mg/L), turbidity (20.29 ± 3.86 NTU), electrical conductivity (EC; 1404.89 ± 114.11 μm/S), and total dissolved solids (TDS; 1150.25 ± 262.10 mg/L) in the salon waste. In the case of bacterial levels, pathogenic bacteria such as fecal coliforms, Escherichia coli, Shigella dysenteriae , and Salmonella enterica were absent, while the levels of Staphylococcus aureus and Pseudomonas aeruginosa did not pose any health risk. The correlation matrix showed a significant positive correlation between and among pH, alkalinity, TDS, and turbidity ( P < 0.05). The results revealed that the wastewater collected from the salon effluents contain pollution indicator parameters such as EC, pH, PO 4 3- , BOD, and turbidity, considerably higher than the tolerance limits recommended by the World Health Organization. The principal component analysis indicated that pH, alkalinity, acidity, COD, PO 4 3- , S. aureus, P. aeruginosa , turbidity, TDS, EC, DO, and BOD were the most influential parameters to wastewater variations. Based on these characteristics, a call for a regular and persistent monitoring strategy by the relevant authorities is significant to ensure best practices with respect to the discharge of salon wastewater into the environment.